Pengaruh Kompetensi SDM, Literasi Keuangan, Modal Keuangan, dan Modal Sosial Terhadap Kinerja UMKM di Kecamatan Tempel - Nisa Hanifah; Hapsari Dyah Herdiany; Natalia Ratna Ningrum (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
One of the most common problems that occurs for MSMEs is in their development. Therefore, it is necessary to pay attention to business performance in order to be able to survive and excel in competition. This study aims to test the influence of human resource competence, financial literacy, financial capital, and social capital on the performance of MSMEs in Tempel District, both partially and simultaneously. The research approach uses a quantitative method with questionnaire instruments distributed to 99 respondents of MSME actors through non-probability sampling techniques. Data analysis was carried out using the SEM-PLS method with the help of SmartPLS 4.1.0.9 software, through outer model testing (validity and reliability test) and inner model (VIF, GoF, R2 test and hypothesis test). Hypothesis testing is carried out through the t-test and the f-test. The results of the study show that partially human resource competence, financial literacy, and financial capital have a significant positive effect on the performance of MSMEs, while social capital has a positive but insignificant effect on the performance of MSMEs. The results of the research simultaneously show that human resource competencies, financial literacy, financial capital, and social capital have a significant effect on the performance of MSMEs. The implications of these findings emphasize the need for strategies to strengthen human resource competence, increase financial literacy, optimize financial capital, and develop social capital to strengthen the competitiveness and sustainability of MSMEs in the research area.